2007
DOI: 10.1093/ecam/nem177
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation, Chemical Composition and Antioxidant Activity of Brazilian Propolis Samples

Abstract: Total phenolic contents, antioxidant activity and chemical composition of propolis samples from three localities of Minas Gerais state (southeast Brazil) were determined. Total phenolic contents were determined by the Folin–Ciocalteau method, antioxidant activity was evaluated by DPPH, using BHT as reference, and chemical composition was analyzed by GC/MS. Propolis from Itapecerica and Paula Cândido municipalities were found to have high phenolic contents and pronounced antioxidant activity. From these extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
117
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(134 citation statements)
references
References 49 publications
8
117
0
9
Order By: Relevance
“…9 More than 300 components have been identified, including phenolic compounds, such as flavonoids, phenolic acids, and phenolic acid esters, the main components of propolis from temperate regions. 10 Among tropical countries, Brazil has the highest chemical diversity of propolis types, such as those that contain phenylpropanoids, prenylated phenylpropanoids (e.g., artepillin C), and sesqui-and diterpenoids, 11 which confer immunostimulatory, antioxidant, anti-inflammatory, and antimicrobial properties, respectively. 12 Studies have shown the potential of propolis against resistant microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…9 More than 300 components have been identified, including phenolic compounds, such as flavonoids, phenolic acids, and phenolic acid esters, the main components of propolis from temperate regions. 10 Among tropical countries, Brazil has the highest chemical diversity of propolis types, such as those that contain phenylpropanoids, prenylated phenylpropanoids (e.g., artepillin C), and sesqui-and diterpenoids, 11 which confer immunostimulatory, antioxidant, anti-inflammatory, and antimicrobial properties, respectively. 12 Studies have shown the potential of propolis against resistant microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of propolis is strongly infl uenced by the type of vegetation visited by the bees and by the season of the year Majiene et al, 2004;Daugsch et al, 2008;Teixeira et al, 2008). Propolis from temperate zones generally consists of 50-60% resins and balsams, 30-40% of wax, 5-10% of essential and aromatic oils, 5% of pollen, and 5% of other substances (Mendoza et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Propolis is a resinous substance, produced from material from various plant species collected by a range of bee species, among them Apis mellifera L. It has a pleasant aroma and a greenish yellow to dark brown color, depending on its origin and the time of collection (MARCUCCI, 1995;BANKOVA et al, 2000;TEIXEIRA et al, 2010;TORETI et al, 2013). Propolis is used by bees for its biological properties, protecting them against attacks from fungi and bacteria; they also use it in preparing aseptic places for the queen bee to lay eggs and in the mummification of invasive insects (MARCUCCI, 1995;BANKOVA et al, 2000;SILVA et al, 2006;LONGHINI et al, 2007;LUSTOSA et al, 2008;BANKOVA, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized as having biological activities, such as anti-microbial (bactericidal and fungicidal), anti- Martini et al inflammatory, cicatrizing, anesthetic, photo-protective, antibiotic, antiviral, antioxidant, immunomodulatory, hypotensive, anti-HIV, anti-carcinogenic and even anti-neoplasic (PEREIRA et al, 2002;BANKOVA, 2005;BANKOVA, 2009;TEIXEIRA et al, 2010). Biological activities of this kind of propolis are attributed to phenolic substances, such as flavonoids, prenylated p-coumaric acids, and lignans (BANKOVA et al, 2000).…”
Section: Introductionmentioning
confidence: 99%